PENGARUH PRICE DISCOUNT, STORE ATMOSPHERE, TERHADAP KEPUTUSAN PEMBELIAN SERTA SHOPPING EMOTION SEBAGAI VARIABEL INTERVENING (Kasus pada Perilaku Konsumen Giant Supermarket, Semarang) - Warahma, Rizki; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to examines the factors that effect purchase decisions at Giant Supermarket. This is based on the Giants Supermarket’s problems those are the decrease of sales volume, the decrease of TOP Brand Index, the decrease of Brand Value, the decrease of Brand Share, and the decrease of the number of outlets in Giant Supermarket. This research was conducted at Giant Supermarket in Semarang, the factors are store atmosphere, price discount, and shopping emotion. These factors are considered to contribute a considerable share in consumer purchase decisions.The population in this research is consumer who have made purchases at Giant Supermarket in Semarang. The sampling technique which used in this research is snowball sampling with the total sample 150 respondents. The analysis tool which used is Structuran Equation Model (SEM).The result shows that the Store Atmosphere has a positive effect on Shopping Emotion, Price Discount has positive effect on Shopping Emotion, Shopping Emotion have positive effect on Purchase Decision.The shopping emotion factor is the most impact in comparison with other factors.